2006
DOI: 10.1016/j.tetlet.2006.03.122
|View full text |Cite
|
Sign up to set email alerts
|

New organic activators for the enantioselective reduction of aromatic imines with trichlorosilane

Abstract: Abstract-N-Picolinoyl-(2S)-(diphenylhydroxymethyl)pyrrolidine was found to work as an organic activator in the reduction of aromatic imines to the corresponding amines by Cl 3 SiH. The highest selectivity was 80%ee. This is the first data showing that N-formyl group is not always essential as N-protecting group of pyrrolidine derivatives for the reduction of imines by Cl 3 SiH.Enantioselective reduction of ketones 1 and imines 2 has been one of recent topics in asymmetric synthesis. 3 A variety of reducing rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(41 citation statements)
references
References 56 publications
1
39
0
1
Order By: Relevance
“…Matsumura's work had previously shown that the deoxy-picoline derivative 24 catalyzed the asymmetric hydrosilylation of N-phenyl ketimine 25 but led to poor selectivity compared to the parent catalyst 23, inferring the need for a hydrogen bond to effectively coordinate with the ketimine substrate, leading to the commonly accepted model shown. 12 In order to compare this effect in the imidazole series, removal of the hydrogen bond acceptor was achieved by methylation of catalyst 17 with sodium hydride and methyl iodide giving the O-Me catalyst 26 in 56% yield (Scheme 3). For comparison purposes, Matsumura's picolinic acid derived catalyst 23 was prepared from commercially available 2-picolinic acid by treating with oxalyl chloride, then reaction with α,α-diphenylprolinol 13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Matsumura's work had previously shown that the deoxy-picoline derivative 24 catalyzed the asymmetric hydrosilylation of N-phenyl ketimine 25 but led to poor selectivity compared to the parent catalyst 23, inferring the need for a hydrogen bond to effectively coordinate with the ketimine substrate, leading to the commonly accepted model shown. 12 In order to compare this effect in the imidazole series, removal of the hydrogen bond acceptor was achieved by methylation of catalyst 17 with sodium hydride and methyl iodide giving the O-Me catalyst 26 in 56% yield (Scheme 3). For comparison purposes, Matsumura's picolinic acid derived catalyst 23 was prepared from commercially available 2-picolinic acid by treating with oxalyl chloride, then reaction with α,α-diphenylprolinol 13.…”
Section: Resultsmentioning
confidence: 99%
“…Since the first chiral Lewis-base derived catalyst was reported in 2001, 1 there have been many variants of catalyst prepared and evaluated; 2,3 selected examples include formamides, [4][5][6][7] sulfinimides, 8,9 pyridines, [10][11][12] and organophosphorus compounds. [13][14][15] The main focus of research from this group has been using an imidazole derived catalyst that has been shown to function as efficiently as the reported analogous picolinoyl series, 16 in addition to being amenable to reductive amination protocols.…”
Section: Introductionmentioning
confidence: 99%
“…[8] Among the most successful Lewis bases used to activate HSiCl 3 are the picolinamides, simply synthesized by connecting picolinic acid to a chiral carbon skeleton. [9] We now wish to report our preliminary results on the application of novel picolinamide-cinchona organocatalysts for the successful highly enantioselective trichlorosilanemediated reduction of ketomines to chiral amines; more-remarkably high turnover frequencies for the hydrosilylation of imines were observed; the catalyst of choice proved to be active even at a loading of only 1 mol-%. The loading was further reduced to 0.5 mol-%, and for very short reaction times (15 min) very impressive asymmetric catalyst efficiency speed values were reached.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, a variety of chiral Lewis base organocatalysts, which have been effectively utilized in several asymmetric hydrosilylation reactions with HSiCl 3 over the past years, [14] were extensively screened to induce chirality in the product. [15] Pleasingly, both chiral picolinoylpyrrolidine [16] (1 b) and N-formyl l-pipecolinamide [17] (1 d) exhibited high catalytic activity, and more importantly, promising enantioselectivity ( (Table 1, entry 6). It seems that the acid additive just supplies a proton, and might not be involved in the key asymmetric reduction step.…”
mentioning
confidence: 99%